Legal regulation of contractual relations of transportation in Ukraine during the XX century - Lukasevych-Krutnyk, Iryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article is devoted to the study of legal regulation of contractual relations of transportation in Ukraine during the twentieth century. A legal analysis of the basic acts of civil legislation regulating the contract of carriage during this period of time, and their influence on the further development of domestic legislation of Ukraine has been done in this article